1999
DOI: 10.1007/s002640050388
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of single segment non-physeal extremity fractures in children

Abstract: Five hundred and fifteen children with single segment non-physeal extremity fractures were retrospectively reviewed. The male to female ratio was 2.7:1. The average age of study group was 9.9+/-4.7 years; 273 fractures (53%) were on the left, 242 (47%) were on the right. A fall was the main cause of the injury in most of the cases (80%). The forearm was the most commonly seen fracture site. Summer was the season when the fracture incidence was the highest. Highest surgical treatment rate (50%) was seen in supr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
2
2
0
2
Order By: Relevance
“…This is linked to increased sports activity in school-aged children. In our study, falls remain the most common mechanism of fractures, which is similar to data reported in children's trauma [1,17] and children's fractures specifically [6,7,9,18,19]. This may be linked to increased sports activity and poor motor coordination.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is linked to increased sports activity in school-aged children. In our study, falls remain the most common mechanism of fractures, which is similar to data reported in children's trauma [1,17] and children's fractures specifically [6,7,9,18,19]. This may be linked to increased sports activity and poor motor coordination.…”
Section: Discussionsupporting
confidence: 88%
“…Children's fractures are subdivided into physeal and non-physeal [6]. While the first injuries the growth plate, the latter does not.…”
Section: Introductionmentioning
confidence: 99%
“…Evidentemente, a primeira delas é o acometimento dos meninos em relação às meninas, como vemos nas Tabelas 1 e 2. Neste trabalho, esta proporção foi de, aproximadamente, três meninos para cada menina (72,5% para 27,4%), o que, de certa forma, está de acordo com a bibliografia consultada (1,4,(5)(6)(7)(8)(9)(10) . Na avaliação dos nossos resultados, em relação à idade dos pacientes, verificamos que aproximadamente 65% das fraturas têm prevalência entre as idades de um e 11 anos, com os restantes 35% ocorrendo nos pacientes com 12 anos e maiores.…”
Section: Discussionunclassified
“…Due to sparse vehicle in our area as compared to urban cities, rate of injury in road traffic accidents might have remained low. In a study by Akatas et al, [16] 80% of patients sustained injury during fall while playing and 20% met with road traffic accident.…”
Section: Discussionmentioning
confidence: 99%